KOORDINASI MUSPIKA DALAM MENUMBUHKAN RASA NASIONALISME MASYARAKAT DI KECAMATAN BADAU - Sagitarisman E.42008036 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
This study aims to find solution of problems faced by the District of Badau local government regarding to coordination ofDistrict head meeting (muspika) in working on activities. The tittle of this research is based on problems that occur in areaof badau border where the people are lack of their nationalism. The focus of this study is what methods and coordinationtechniques are applied by the body (muspika) of Badau District.Keyword : Coordination, Muspika, Nationalism